2007
DOI: 10.1111/j.1365-313x.2006.03001.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐random distribution of T‐DNA insertions at various levels of the genome hierarchy as revealed by analyzing 13 804 T‐DNA flanking sequences from an enhancer‐trap mutant library

Abstract: SummaryWe isolated 13 804 T-DNA flanking sequence tags (FSTs) from a T-DNA insertion library of rice. A comprehensive analysis of the 13 804 FSTs revealed a number of features demonstrating a highly nonrandom distribution of the T-DNA insertions in the rice genome: T-DNA insertions were biased towards large chromosomes, not only in the absolute number of insertions but also in the relative density; within chromosomes the insertions occurred more densely in the distal ends, and less densely in the centromeric r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 51 publications
(61 reference statements)
7
75
0
1
Order By: Relevance
“…Our study showed that the distribution of T-DNA insertions was correlated with the chromosome size, which is consistent with previous reports that T-DNA insertions are not randomly distributed on the chromosomes [57,58]. The larger chromosomes contain more T-DNA insertions and also show higher insertion density (Table 1; Supplementary information, Figure S1).…”
Section: Distribution Of T-dna Insertions On Chromosomessupporting
confidence: 81%
“…Our study showed that the distribution of T-DNA insertions was correlated with the chromosome size, which is consistent with previous reports that T-DNA insertions are not randomly distributed on the chromosomes [57,58]. The larger chromosomes contain more T-DNA insertions and also show higher insertion density (Table 1; Supplementary information, Figure S1).…”
Section: Distribution Of T-dna Insertions On Chromosomessupporting
confidence: 81%
“…The osbc1l4 mutant exhibited a dwarf and less tiller phenotype The osbc1l4 mutant line was identified from our T-DNA insertion Rice Mutant Database (RMD; http://rmd.ncpgr.cn/; Wu et al 2003;Zhang et al 2007). The mutant exhibited a d Wild type (left) and OsBC1L5/osbc1l5 (right) heterozygous plants at maturity stage.…”
Section: Identification and Characterization Of Osbc1l Insertion Mutantsmentioning
confidence: 99%
“…A BLASTn search of the T-DNA flanking sequence isolated by thermal asymmetric interlaced PCR (Zhang et al, 2007) against the rice genomic sequence database (http://rice.plantbiology.msu.edu) showed that the T-DNA was inserted into the intron of OsRPA1a (LOC_Os02g53680; Fig. 2A), which encodes RPA1a, one of the isoforms of RPA1 subunit in rice (Ishibashi et al, 2006).…”
Section: Isolation and Characterization Of The Osrpa1a Genementioning
confidence: 99%